The direct relationship between earnings management and cost of capital in Jordan’s companies - Saidin, Saidatunur Fauzi; Ghaleb Al-qadi, Maher Azzam; Abdul-hamid, Mohamad Ali (IJAAFMR, 2024)
The direct relationship between earnings management and cost of capital in Jordan’s firms has a very vital role to play in earnings management and sources of financing in Asian. In spites of its importance, there is a serious dearth of literature on earnings management and cost of capital especially in Asian, particularly in Jordan. Therefore, the objective of this study is to investigate the effect of earnings management on cost of capital in Amman stock exchange. However, the method that influences the expectations of investors are the firms that need to be credible, transparent, and more informative about their activities, because when the firms’ stocks have more liquid, the ability to attract investors will increase and it will obtain the necessary funds for their various activities. The study employed panel data analysis to an initial sample of 191 listed companies in the Amman Stock Exchange (ASE) covering 10-years period between 2010-2019. However, we sampled 99 nonfinancial listed companies on the Jordan Stock Exchange. Therefore, the findings from the panel data regression analysis revealed that, the real earnings management and accrual earnings management were significantly positively related to firms performance, which suggests that the shorter the periods the higher the performance of the companies. In the same vain, the control variables such as Firm’s Size and return on assets were positively significant. However, Leverage is insignificant to the cost of capital. Finally, the study provides managerial implications and the direction for future research